2021
DOI: 10.3390/molecules26040781
|View full text |Cite
|
Sign up to set email alerts
|

A 60% Edible Ethanolic Extract of Ulmus davidiana Inhibits Vascular Endothelial Growth Factor-Induced Angiogenesis

Abstract: As abnormal angiogenesis is associated with exacerbation of various diseases, precise control over angiogenesis is imperative. Vascular endothelial growth factor (VEGF), the most well-known angiogenic factor, binds to VEGF receptor (VEGFR), activates various signaling pathways, and mediates angiogenesis. Therefore, blocking the VEGF-induced angiogenic response-related signaling pathways may alleviate various disease symptoms through inhibition of angiogenesis. Ulmus davidiana is a safe natural product that has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
2
0
0
Order By: Relevance
“…The two main causes of DR are retinal vascular leakage and abnormal retinal angiogenesis ( 27 ). Interestingly, through previous study ( 25 ) and this study, almost all in vitro experiments confirmed that U60E or C7A prevent both retinal vascular leakage and retinal angiogenesis in the condition of DR. These are interesting results that U60E or C7A can block both major causes of DR.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The two main causes of DR are retinal vascular leakage and abnormal retinal angiogenesis ( 27 ). Interestingly, through previous study ( 25 ) and this study, almost all in vitro experiments confirmed that U60E or C7A prevent both retinal vascular leakage and retinal angiogenesis in the condition of DR. These are interesting results that U60E or C7A can block both major causes of DR.…”
Section: Discussionsupporting
confidence: 83%
“…In this study, we investigated the effect of U60E on endothelial permeability in DR. In our previous studies, we confirmed that U60E prevents VEGF-induced endothelial cell proliferation, tube formation, and migration; therefore, we hypothesized that U60E could be an effective treatment for retinopathy caused by abnormal angiogenesis, such as proliferative DR ( 25 ). However, the effect of U60E on endothelial permeability, another major cause of DR, is unknown.…”
Section: Discussionsupporting
confidence: 54%